2013
DOI: 10.1016/j.virusres.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated phenotypes of primary murine alveolar epithelial cells and their susceptibility to infection by respiratory viruses

Abstract: Severe respiratory viral infections are associated with spread to the alveoli of the lungs. There are multiple murine models of severe respiratory viral infections that have been used to identify viral and host factors that contribute to disease severity. Primary cultures of murine alveolar epithelial cells provide a robust in vitro model to perform mechanistic studies that can be correlated with in vivo studies to identify cell type-specific factors that contribute to pathology within the alveoli of the lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…The presence of the cleaved HA protein in cell lysates suggests that differentiated ATII cells are capable of post-translational processing of HA, which is required for viral infectivity and correlates with virulence of IAV strains (Blazejewska et al, 2011; Steinhauer, 1999). These data are in agreement with our previous study that demonstrated productive infection of murine ATII cells by PR8 (Kebaabetswe et al, 2013). Infection of primary murine ATII cells provides a robust system for analysis of PR8-regulated changes to the cellular proteome in physiologically relevant target cells.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…The presence of the cleaved HA protein in cell lysates suggests that differentiated ATII cells are capable of post-translational processing of HA, which is required for viral infectivity and correlates with virulence of IAV strains (Blazejewska et al, 2011; Steinhauer, 1999). These data are in agreement with our previous study that demonstrated productive infection of murine ATII cells by PR8 (Kebaabetswe et al, 2013). Infection of primary murine ATII cells provides a robust system for analysis of PR8-regulated changes to the cellular proteome in physiologically relevant target cells.…”
Section: Resultssupporting
confidence: 94%
“…Primary cultures of murine ATII cells are not homogenously susceptible to PR8 infection, as can be seen by heterogeneous staining of viral antigens in our cultures (Fig. 1A) (Kebaabetswe et al, 2013). Therefore, it is possible that the IFN-stimulated proteins we are detecting come from either infected or uninfected cells within the culture.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations